A novel single-phase Na3.6Y1.8(PO4)3:Bi3+, Eu3+ phosphor for tunable and white light emission. Issue 1 (1st January 2021) - Zhang, WenNa; Tong, Ye; Hu, FangFang; Wei, RongFei; Chen, LiPing; Guo, Hai
Abstract: A new type of Bi 3+, Eu 3+ single- and co-doped Na3.6 Y1.8 (PO4 )3 phosphate phosphors were manufactured using conventional high-temperature solid-state reaction technique to explore their application for solid-state lighting. The crystal structure, luminescent properties, luminescent mechanism and quantum efficiency were thoroughly explored. Results show that there are two crystallization sites for Bi 3+ and Eu 3+ ions. Upon the excitation of 342 and 373 nm, Bi 3+ single-doped phosphors exhibit green and blue emission, derived from the 3 P1 to 1 S0 transition of Bi 3+ located in different occupancy sites. Thanks to radiative energy transfer process from Bi 3+ to Eu 3+, adjustable emission could be acquired by altering Eu 3+ content in co-doped phosphors. Pure white-light emission with quantum efficiency value of 22.9% can be realized in Na3.6 Y1.8 (PO4 )3 :0.01Bi 3+, 0.1Eu 3+ sample and the integrated intensity of white light emission at 417 K remains 85% of that at room temperature. Our results indicate that Na3.6 Y1.8 (PO4 )3 :Bi 3+, Eu 3+ phosphors have feasible application in high-power ultraviolet driven solid-state lighting.